On the Normative Paradigm of Sworn Translation in the Realm of Law - Król, Małgorzata Z. (Research in Language, 2020)
In the 1920s the Polish legislature adopted a whole range of normative acts focused on the protection of the Polish language and on sworn translators practicing in official contexts. In accordance with statutory law, since 2004 sworn translators have been considered a profession commanding public trust. Among the many professional duties associated with sworn translators' performance, the regulations emphasize the duty to translate both spoken discourse and written texts with precision and faithfulness, and make sworn translators liable to disciplinary sanctions for poor quality work. The principles and rules for practicing the profession of sworn translator are enumerated in the Professional Sworn Translator’s Code of 2018.